Pengaruh Pengembangan Karir Dan Self Efficacy Terhadap Kinerja Karyawan Di CV. Danagung D’ Briquettess Bantul Yogyakarta - Amaliya Dwi Anjani (EKONOMI DAN BISNIS DIGITAL, 2023)
This study aims to examine the Effect of Career Development and Self Efficacy. Against the performance of employees at CV. Danagung D'Briquetess Bantul Yogyakarta. This study uses a saturated sample because of the small population in this company. Data collection techniques using questionnaires distributed through company owners. Methods of data analysis using data quality test, classical assumption test, multiple linear regression test and the coefficient of determination. The results of this study indicate that the variables Career Development and Self Efficacy have a positive and significant effect on Employee Performance. The most dominant influence is Self- Efficacy followed by Career Development